Prevalence of POC5 Coding Variants in French-Canadian and British AIS Cohort - Mathieu, Hélène (Genes (Basel), 2021)
Adolescent idiopathic scoliosis (AIS) is a complex common disorder of multifactorial etiology defined by a deviation of the spine in three dimensions that affects approximately 2% to 4% of adolescents. Risk factors include other affected family members, suggesting a genetic component to the disease. The POC5 gene was identified as one of the first ciliary candidate genes for AIS, as three variants were identified in large families with multiple members affected with idiopathic scoliosis. To assess the prevalence of p.(A429V), p.(A446T), and p.(A455P) POC5 variants in patients with AIS, we used next-generation sequencing in our cohort of French-Canadian and British families and sporadic cases. Our study highlighted a prevalence of 13% for POC5 variants, 7.5% for p.(A429V), and 6.4% for p.(A446T). These results suggest a higher prevalence of the aforementioned POC5 coding variants in patients with AIS compared to the general population.